Design and implementation of neural network based conditions for the CMS Level-1 Global Trigger upgrade for the HL-LHC - Bortolato, G.; Cepeda, M.; Heikkilä, J.; Huber, B.; Leutgeb, E.; Rabady, D.; Sakulin, H. (Journal of instrumentation, 2024)
The CMS detector will be upgraded to maintain, or even improve, the physics acceptance under the harsh data taking conditions foreseen during the High-Luminosity LHC operations. In particular, the trigger system (Level-1 and High Level Triggers) will be completely redesigned to utilize detailed information from sub-detectors at the bunch crossing rate: the upgraded Global Trigger will use high-precision trigger objects to provide the Level-1 decision. Besides cut-based algorithms, novel machine-learning-based algorithms will also be included in the Global Trigger to achieve a higher selection efficiency and detect unexpected signals. Implementation of these novel algorithms is presented, focusing on how the neural network models can be optimized to ensure a feasible hardware implementation. The performance and resource usage of the optimized neural network models are discussed in detail.